IMPLEMENTASI ENVIRONMENTAL LITERACY DI SD NEGERI BAKALAN BANTUL - Elsi Oktarina; Kristi Wardhani; Endah Marwanti (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2020)
This research was descriptively aimed to find out how the implementation of environmental literacy in SD Negeri Bakalan Bantul was. This study was a qualitative approach, which was carried out at SD Negeri Bakalan Bantul by selecting the school principal as the key informant, then the school principal chose several fellow teachers and the teachers chose students as subjects or research samples. This study employed a qualitative descriptive method. Data collection techniques in this study were interviews, observation and documentation. The instrument in this study was the researcher himself. The technique of determining the sample of data sources used snowball sampling. The results of the descriptive study indicated that the implementation of environmental literacy at SD Negeri Bakalan Bantul had been carried out well. The manifestation of environmental literacy implementation in these schools was through the development of the school learning curriculum, the development of the learning process, and the development of the health of the school environment. The implementation of environmental literacy at SD Negeri Bakalan Bantul encompassed the implementation of environmental literacy through school subjects, environmental health practices through farming and maintaining environmental cleanliness with classroom pickets and mutual cooperation, plastic waste processing and waste banks. Thus, the implementation of environmental literacy at SD Negeri Bakalan Bantul had been good, as it was proven with the award of adiwiyata school.